Ceramic Materials from Coffee Bagasse Ash Waste - Acchar, Wilson (Springer, 2015)
This book proposes the use of coffee bagasse ash (CBA) waste as raw material to be used in ceramic formulations. The approach presented here is a solution to a current ambiental problem as CBA waste is discharged in high amounts in agriculture. The authors analyze the potencial of CBA as a material to substitute feldspar in tile production.